Infections in crush syndrome: a retrospective observational study after the Wenchuan earthquake. Issue 1 (8th September 2010) - Xiaolei, Chen; Hui, Zhong; Ping, Fu; Zhangxue, Hu; Wei, Qin; Ye, Tao
Abstract : Objectives: To investigate the characteristics of infections in the casualties with crush syndrome after the Wenchuan earthquake. Methods: The clinical data of patients during their first 2 months of hospitalisation were analysed retrospectively. 58 crush syndrome patients were included. Demographic data, physical and laboratory findings, treatment and outcome were recorded. Results: The mean age of these patients was 32.8±20.7 years and the average duration under the rubble was 23.7±19.3 h. Fasciotomy and amputation were performed in 29 (50%) and 34 (58.6%) patients, respectively. Renal replacement therapies were administered to 47 patients (81%). Four patients died while all the others restored their renal function. Microbial pathogens were detected in the samples from 39 patients (67.2%), 26 of whom developed sepsis. The most vulnerable sites for infection were wounds (55.2%) and lungs (37.9%). Acinetobacter baumanii and Pseudomonas aeruginosa were the most common bacterial isolates from wound infections. 26 of 39 patients (66.7%) became infected after 48 h of admission. The infected group had a longer duration under the rubble (39.2 h vs 30.1 h, p=0.000) and more fasciotomies (61.5% vs 26.3%, p=0.012) compared with those without infections. Multivariate analysis indicated that duration under the rubble (p=0.012, OR 1.061), duration of renal impairment (p=0.015, OR 1.096) and fasciotomy (p=0.024, OR 5.470) were risk factors for infection. Conclusions: Infectious complications are common in crush syndrome. In order to improve patient outcomes, vigorous care and strict surveillance are required.